Quantum phase transition properties of the Heisenberg antiferromagnet with single-ion anisotropy using 2d/3d isotropic and DTN parameters. - Yap, Ian Ching Loong. (2011)
A brief introduction to the physics of the QPT for our Hamiltonian is presented together with the tools required to analyze the QPT. The SSE QMC method is outlined together with specific implementation details for running on a supercomputer. We obtain the critical values of D at zero magnetic field using parameters for the 2d/3d isotropic and the organic compound DTN and obtain the ground-state hz − D phase diagram for the isotropic lattices. Results suggest that using d and z in the finite-size scaling relations for spin stiffness at and above the upper critical dimension give a good (if not correct) value of Dc but MFT exponents may not characterize the transition.